A Novel Solution‐Processable n‐Dopant Based on 1, 4‐Dihydropyridine Motif for High Electrical Conductivity of Organic Semiconductors. (17th August 2017) - Shi, Ke; Lu, Zuo‐Yu; Yu, Zi‐Di; Liu, Han‐Yu; Zou, Ye; Yang, Chi‐Yuan; Dai, Ya‐Zhong; Lu, Yang; Wang, Jie‐Yu; Pei, Jian
Abstract: p‐ or n‐Dopants have played significant roles in the improvement of organic electronic devices through the controllable doping of organic semiconductors. However, there has been little study of air‐stable n‐dopants under ambient conditions with strong doping capability due to the low electron affinities of organic semiconductors. Herein, a 1, 4‐dihydropyridine‐based derivative is designed and facilely synthesized as an efficient n‐dopant. The doping process is systematically investigated by UV–vis–NIR spectroscopy in solution and ultraviolet photoelectron spectroscopy in the solid state. Excellent conductivities are obtained for a variety of doped n‐type semiconductors via a simple solution process without further treatment, suggesting a broad class of 1, 4‐dihydropyridine derivatives could be used as n‐dopants in future organic electronic devices. Abstract : A novel organic n‐dopant, DPDHP, is developed and electrical conductivity measurements demonstrate effective doping with a variety of n‐type semiconductors via a simple solution process. This is the first example of the application of 1, 4‐dihydropyridine‐based compounds as solution‐processed n‐dopants.